Evaluation of level of physical and anthropometric indices of pregnant women at the end of 1st trimester of pregnancy attended in basic health units of a municipality of Minas Gerais, Brazil (Research, Society and Development, 2025)
The aim of the study was to evaluate anthropometric indices and physical activity levels (PAL) of pregnant women at the end of the 1st trimester of pregnancy treated at basic health units (BHU), especially body mass index (BMI), arm circumference (AC) and PAL classification. This is an observational, cross-sectional study, with data collection during the prenatal period, as part of a cohort study. A convenience sample of pregnant women at the end of the 1st trimester of pregnancy treated at a UBS in the municipality of Divinópolis, Minas Gerais, was used. The project was approved by the Research Ethics Committee of the State University of Minas Gerais. Pregnant women were evaluated between the 13th and 16th weeks, with the BMI obtained using measurements of AC, height, weight, in addition to the PAL. The pregnant women evaluated were overweight/obese in 63.7% and 36.4%, respectively, according to BMI and AC. 45.5% were sedentary or irregularly active, 9.1% were underweight and 54.5% had adequate nutritional status through AC assessment, different from BMI (27.3%). It is concluded that there were different diagnoses of overweight/obesity when BMI and AC were used and that a small proportion were underweight. The average BMI at the end of the first trimester of pregnancy was lower than some Brazilian studies, but AC was higher than others. Almost half of the volunteers were sedentary or irregularly active, although lower than some Brazilian studies.